ダイ10ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク - 石田, 恭市; イシダ, キョウイチ; 鈴木, 剛彦; スズキ, タケヒコ; 酒井, 重典; サカイ, シゲノリ; ISHIDA, Kyoichi; SUZUKI, Takehiko; SAKAI, Shigenori (国立極地研究所, 1971)
P(論文) The authors were members of the 10th Japanese Antarctic Research Expedition and were responsible for meteorological observations at Syowa Station between 1 February, 1969 and 31 January, 1970. The main subjects of observations, the method, and the equipments remain almost unchanged since 1966. The data of the surface observation at 00, 06, 12, 18 GMT and the aerological observation at 00 GMT were reported to Melbourne via Mawson according to the WMO Regulations. Observations of the ground temperature at 50 cm and 90 cm deep, the amount of ozone at the surface, and the total amount of ozone, especially in winter, were also carried out. Characteristics in this season were : 1) The monthly mean temperatures till June were 1-2℃ higher than the normal year. 2) The annual amount of the precipitation was less than the normal year. 3) Stratowarming was noticed from 27 October to 1 November, with temperature about -45℃ at 50 mb (20 km) level. departmental bulletin paper